Forests and water: a policy perspective - Kaimowitz, D. (2004)
Asian policymakers need to know how changes in land uses and practices related to forests affect flooding, dry season stream flow, and water quality. Based on their beliefs about these relations, policymakers often ban logging or introduce expensive projects. Many key stakeholders believe that logging and deforestation increase flooding and the damage floods cause, but there is only evidence for this in relation to smaller and less severe floods. It is also widely believed that logging and clearing forest reduce dry season stream flow, but whether that actually occurs depends on rainfall patterns, soils, topography, geology, and the type of vegetation. Forests generally improve water quality, although not always. More research is needed on the magnitude of the water quality effects, particularly as regards drinking water.